2021
DOI: 10.1080/23802359.2021.1899078
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genome characterization of Gryllodes sigillatus (Orthoptera: Gryllidae) and its phylogenetic implications

Abstract: Gryllodes sigillatus is a cricket widely distributed throughout the world. In this study, we reported the first complete mitogenome sequence of Genus Gryllodes and inferred its phylogeny. The mitogenome of G. sigillatus was 16,369 bp and consisted of a control region and a typical set of 37 genes. It was ATrich with strong codon usage bias and possessed a gene arrangement of trnE-trnS1-trnN. Phylogenetic analysis indicated G. sigillatus was sister species to Velarifictorus hemelytrus, together belonging to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…2). Recent studies using the mitochondrial genome and a combination of nuclear and mitochondrial genes have shown that Grylloidea and Gryllotalpoidea are monophyletic sister groups (Song et al 2015;Chintauan-Marquier et al 2016;Zhou et al 2017;Yang et al 2021;Sanno et al 2021). However, other studies or approaches have either not confirmed this relationship or have produced conflicting phylogenetic relationships (Song et al 2020;Sanno et al 2021).…”
Section: Gryllideamentioning
confidence: 99%
“…2). Recent studies using the mitochondrial genome and a combination of nuclear and mitochondrial genes have shown that Grylloidea and Gryllotalpoidea are monophyletic sister groups (Song et al 2015;Chintauan-Marquier et al 2016;Zhou et al 2017;Yang et al 2021;Sanno et al 2021). However, other studies or approaches have either not confirmed this relationship or have produced conflicting phylogenetic relationships (Song et al 2020;Sanno et al 2021).…”
Section: Gryllideamentioning
confidence: 99%
“…To do so, we fit mixed‐effects models with the same fixed effects, prior structure and chain parameters as mentioned before but omitting species as a fixed effect. Species was instead incorporated as a random effect, along with individual ID, with the relationship among species modelled according to the current phylogeny (Figure 1; Gray et al, 2020; Yang et al, 2021). All nodes in our phylogeny had high support (≥95%) in prior phylogenetic analyses (Gray et al, 2020; Yang et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Species was instead incorporated as a random effect, along with individual ID, with the relationship among species modelled according to the current phylogeny (Figure 1; Gray et al, 2020; Yang et al, 2021). All nodes in our phylogeny had high support (≥95%) in prior phylogenetic analyses (Gray et al, 2020; Yang et al, 2021). Although Gray et al (2020) provided divergence times, these were estimated with high uncertainty and unavailable across genera.…”
Section: Methodsmentioning
confidence: 99%
“…CC-BY 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted September 22, 2022. ; https://doi.org/10.1101/2022.09.21.508865 doi: bioRxiv preprint groups to Gryllidae in other studies (40,41). We found Tettigoniidae paraphyletic with respect to a clade consisting of Anostostomatidae (Hemideina) + Rhaphidophoridae (Ceuthophilus + Hadenoecus) that is placed as sister group to Meconematinae, albeit with poor support of 70% Bootstrap (Supplementary File 1).…”
Section: The Evolution Of Genome Sizementioning
confidence: 56%